Technology, Typology, and Evolution of Egyptian Pottery at Kom al-Ahmer/Kom Wasit (Near Alexandria) - Mondin, Cristina (Rei Cretariae Romanae Fautorum Acta, 2024)
The Egyptian pottery found at the sites of Kom al-Ahmer and Kom Wasit in the western Delta shows recurring characteristics in terms of technology and shape. The alluvial clay products can be divided into two macro-groups. The first, using technology that comes directly from ancient Egyptian Dynastic traditions, is characterised by the abundance of organic inclusions. The second, introduced at the beginning of the Hellenistic period, shows the influence of cooking and table-ware shapes from the Aegean-Mediterranean tradition, which led to a change in fabric and technology. The new technology concerns the introduction of kick-wheels that allow for a more regular modelling, facilitating the standardisation of pottery production. The new forms were produced continuously until the Roman times, until the 3rd century AD, when new forms of coarse ware were introduced.